Stability and Antibiofilm Efficiency of Slightly Acidic Electrolyzed Water Against Mixed-Species of Listeria monocytogenes and Staphylococcus aureus - Yan, Pianpian; Chelliah, Ramachandran; Jo, Kyoung-hee; Selvakumar, Vijayalakshmi; Chen, Xiuqin; Jo, Hyeon-yeong; Oh, Deog Hwan (Frontiers in Microbiology, 2022)
In the natural environment, most microorganisms live in mixed-species biofilms, in which the metabolism and growth of organisms are different from that in single-species biofilms. Adhesive bacteria and their biofilms on the surface of food processing equipment are the sources of cross-contamination, leading to the risk for humans. Slightly acidic electrolyzed water (SAEW) has been proposed as a novel sanitizer in the food and agriculture industry. In this study, we investigated the changes in the physical properties of SAEW under different conditions and the disinfection abilities of SAEW against spore-forming and non-spore-forming pathogens. Furthermore, we examined the disinfection abilities of SAEW after 12 months of shelf life on a mixed-species biofilm of Listeria monocytogenes Scott A and Staphylococcus aureus. The results showed that SAEW at 30 and 50 ppm achieved all-kill of the spore-forming pathogen Bacillus cereus within 30 s. Changes in the ACC and pH of the produced SAEW were generally affected by the storage conditions. Both spore-forming and non-spore-forming pathogens were not detected under treatment with 50 ppm SAEW for 5 min under HDPE-closed conditions throughout the whole storage period. Moreover, 25 mg/L SAEW can inactivate L. monocytogenes Scott A and S. aureus biofilm cells in 2.45 and 2.57 log CFU/mL in biofilms within 5-min treatment. However, the decline of the two bacteria in the mixed-species biofilm was 1.95 and 1.43 log CFU/mL, respectively. The changes in the cell membrane permeability of the mixed-species biofilm under treatment with SAEW were observed by using atomic force microscopy and confocal laser scanning microscopy. L. monocytogenes Scott A was more sensitive to SAEW in the mixed-species biofilm cells. These findings exhibited strong antibiofilm activities of SAEW in impairing biofilm cell membranes, decreasing cell density, and eliminating biofilm, which suggest that SAEW is an excellent antibacterial agent in the food processing industries.